Adjuvants influence the immune cell populations present at the injection site granuloma induced by whole-cell inactivated paratuberculosis vaccines in sheep - Criado, Miguel; Reyes, Luis E.; Marín, Juan F. García; Gutiérrez-Expósito, Daniel; Zapico, David; Espinosa, José; Pérez, Valentín (Frontiers in Veterinary Science, 2024)
Vaccination is the most effective tool for paratuberculosis control. Currently available vaccines avoid the progression to clinical disease in most animals, but do not fully protect against infection and induce the formation of an injection site granuloma. The precise mechanisms that operate in the response to vaccination and granuloma development, as well as the effect that adjuvants could have, have not been fully investigated. Thus, the aim of this work was to study the injection site granulomas induced by two inactivated paratuberculosis vaccines, which differ in the adjuvant employed. For that, two groups of 45-day-old lambs were immunized with two of the commercially available vaccines: one (n = 4) with Gudair ® and the other (n = 4), with Silirum ® . A third group (n = 4) was not vaccinated and was kept as control. The peripheral humoral and cellular immune responses were assessed throughout the study by a commercial anti-Mycobacterium avium subspecies paratuberculosis (Map) antibody indirect ELISA and the IFN-γ release and comparative intradermal tests, respectively. The injection site granulomas were measured during the experiment, and sampled at 75 days post-vaccination (dpv), when the animals were euthanized. Then, the tissue damage, antigen and adjuvant distribution and the presence and amount of immune cells, determined by immunohistochemical methods, were assessed. Antibodies against Map antigens, a general macrophage marker (Iba1), M1 (iNOS) and M2 (CD204) macrophages, T (CD3), B (CD20) and γδ T lymphocytes, the proteins MHC-II, NRAMP1, and the cytokines IL-4, IL-10, TNF and IFN-γ were employed. Silirum ® elicited a stronger peripheral cellular immune response than Gudair ® , while the latter induced larger granulomas and more tissue damage at the site of injection. Additionally, adjuvant and Map antigen distribution throughout the granulomatous inflammatory infiltrate, as well as the NRAMP1 cell expression, which is linked to antigen phagocytosis, were highly irregular. In Silirum ® induced granulomas, a higher number of MHC-II and TNF expressing cells, and a lower number of M2 macrophages, suggests an improved antigen presentation, which could be due to the better antigen distribution and reduced tissue damage induced by this vaccine.